A Comparative Study of the Financial Performance of the three Banking Modes in Egypt: Islamic, Conventional and Mixed Banks - Abdeldayem, Marwan M.; El-Sherbiney, Radwa A. (Archives of Business Research, 2018)
The purpose of this study is to examine and compare the financial performance of the three banking modes in Egypt: Islamic, conventional and mixed banks during the period 2003-2010. 13 banks are included in the study (i.e. 2 Islamic banks, 8 conventional banks, and 3 mixed banks). Multiple regression models are used to study the influence of both the internal bank-specific characteristics and the external macroeconomic environment on the performance of the three types of banks in Egypt. Return on assets (ROA) and return on equity (ROE) are employed to measure the performance of the three types of banks in Egypt. Moreover, a set of internal and external factors are considered as independent variables including; liquidity, capital adequacy, asset quality, operation efficiency, bank's size, GDP growth rate (GDP GR), and inflation rate. The findings reveal that operation efficiency has a significant negative impact on the three types of banks in Egypt, while bank's size and inflation rate have a significant influence merely on the performance of conventional banks. In addition, capital adequacy and asset quality have a positive significant influence on the performance of mixed banks. Furthermore, the comparison between financial performances of the three types of banks indicates that there is a significant difference between both ROA and ROE of Islamic banks and conventional banks, and the performance of conventional banks is better than the performance of Islamic banks in Egypt. On the other hand, there is no significant difference between the performance of Islamic banks and mixed banks, while there is a significant difference between ROA of conventional banks and mixed banks and no significant difference between ROE of conventional and mixed banks. The study also identifies the most significant indicators that contribute to assessing the performance of the three banking modes in Egypt.